Heart-lung transplantation: pediatric indications and outcomes - Spahr, Jonathan E. (Pioneer Bioscience Publishing Company, 2014)
As indications for heart-lung transplant (HLT) have changed to some degree in the past 30 years, this treatment is being used less frequently in children due to more advanced care of severe heart and lung disease. This is fortunate as the outcomes for HLT are poor compared to other solid organ transplants and this is mainly due to the poorer outcome of the lung graft.